Frequency of drug resistant Salmonella spp. isolated from poultry samples in Bangladesh - Akond, Muhammad Ali; Shirin, Momena; Alam, Saidul; Hassan, SMR; Rahman, Md Mahbubur; Hoq, Mozammel (Stamford Journal of Microbiology, 2013)
Present study was conducted to determine the levels of Salmonella spp. mediated contamination in samples collected from poultry and poultry environments in Bangladesh and to determine the antibiotic resistance trait in those pathogens. A total of 300 samples were collected from five different sources (cloacal swab, intestinal fluid, egg surface, hand wash of chicken handler and soil of chicken market) and 80 (26.6%) samples were found to be contaminated with Salmonella spp. One hundred and fifty Salmonella strains were isolated among which, 91 were detected as S. enteriditis and 59 as S. typhimurium through morphological, biochemical and serological tests. Susceptibility of the isolates against 13 antimicrobials was tested, and resistance against chloramphenicol (30 ?g), erythromycin (15 ?g), ampicillin (10 ?g), riphampicin (5 ?g), cephalexin (15 ?g), cefixine (5 ?g), penicillin (10 ?g), tetracycline (30 ?g), norfloxacin (10 ?g), nalidixic acid (30 ?g) and ciprofloxacin (10 ?g) was found in 58%, 82%, 88%, 60%, 65%, 50%, 100%, 100%, 20%, 20% and 20% of the strains, consecutively. 76% isolates were found to be sensitive against gentamicin and 70% against streptomycin. Some of the isolates interestingly exhibited multiple-drug resistances against at least 6 to 10 antibiotics. The results indicated the higher resistance of Salmonella spp. against antibiotics which serving as a threat not only to poultry industry of Bangladesh but also possesses a serious threat to public and animal health. DOI: http://dx.doi.org/10.3329/sjm.v2i1.15207 Stamford Journal of Microbiology, Vol.2(1) 2012: 15-19